On the Question of Circumstances, Reasons and Date of Tigranes the Great Extradition as Hostage to the Parthians. A Revised Armenian Chronology of the Period 215-96 BC - Ruslan Kobzar (Banber Arevelagitut'yan Instituti)
This article re-examines the circumstances, reasons and date of taking Tigranes II the Great into hostage by the Parthians from a new perspective. In the light of in-formation from late Babylonian cuneiform, Greco-Roman, ancient Armenian and ancient Georgian sources, the prevailing scholarly opinion that the surrender of Prince Tigranes as a hostage was due to the demands of the Parthian side following the Armenian military defeat by Parthian King Mithridates II is challenged and refuted. A new interpretation of events logically connects the accounts of Justin [25:322] and Strabo [42:336-340] regarding taking Tigranes II the Great hostage, which is confirmed by the late Babylonian cuneiform tablet, with information from Strabo [43:224-225] of successful Armenian resistance against repeated Parthian aggression.